Investigation of Adhesion Molecules in the Placentas of Patients with Gestational Diabetes Mellitus with Premature Rupture of Membranes - Sancar , Muhyiddin; Atiç , Esranur; Karabat , Mehmet Uğur; Kaplan , Şehmus; Aktaş , Ayfer; Aşır, Fırat (Journal of Drug Delivery and Therapeutics, 2025)
Aim: The aim of this study was to examine the histopathological changes in the placentas of patients with Gestational Diabetes Mellitus (GDM) and premature rupture of membranes (PROM). Materials and Methods: Placentas of 21 GDM+PROM and 21 healthy pregnant women were sectioned into 4-6 μm sections and stained with Hematoxylin-Eosin. Results: In GDM+PROM group, fibrinoid deposition in light pink areas, degeneration of chorionic villi and irregularities in villus structure, congestion and dilatation of capillary vessels were observed. Leukocyte infiltration was observed in the intervillous area. Desidua cells showed degeneration and pycnosis. Rupture of the amniotic membrane was observed. Conclusion: We have demonstrated that GDM+PROM leads to severe pathologic changes in placental structures and is associated with inflammatory and vascular dysfunction. Keywords: Gestational diabetes mellitus, premature rupture of membranes, placenta